Analysis of Higher Education Counselling and its awareness among Higher Secondary Students in Tamil Nadu, India - P. Amutha, Dr. R. Priya (International Journal of Modern Agriculture, 2021)
The significant aim of career counselling is to provide information and guidance regarding students’ educational plans and personality development to attain the successful completion of their higher education. Today, gleaning out the knowledge about the appropriate course is one of the most important and crucial tasks for post-secondary students. This research work examined the knowledge about higher education courses amongst secondary students and the importance of career counselors in higher secondary school to go around the right decision. The cross-sectional analysis was conducted using the well-structured questionnaire which was developed and adapted from previous studies. The data wasanalyzed using R studio, Product Version 1.3.1098.0. The attributes were cross-tabulated to find out their associations. This study concluded that most of the students have knowledge about their subject selection but they are surely concerned with getting appropriate guidance. This study also revealed that a very few schools had a counselor and providedonly few course counselling sessions for their students. The students suggested course counselling to be really important todetermine their future career pathby efficient recommendations system or by the human counselors.